METODE BRIEFING, GROUPING, GAMES AND TURNAMENT, REWARD(BRIGGATURE) SEBAGAI UPAYA MENINGKATKAN MOTIVASI ANAK JALANANUNTUK MENEMPUH WAJIB BELAJAR 9 TAHUN DI YOGYAKARTA - Ismiati Sholikha, Laifa Rahmawati, Noviana Anjar Hastuti (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
Primary education must be adopted by all citizens. It means that education is right andobligation for children aged 7 – 15 years, including street children. However, they like hangingaround in the street in the school hours. Without their own motivation, the government’s program toovercome the issue of education will not run well. Therefore, it is required a method to increase theirmotivation to study.Briefing method, Grouping, Games and Tournament, Reward (BRIGGATURE) are efforts toovercome the lack of street children’s motivation toward the 9‐years compulsory education. Briefingmethod is a step of delivering materials and affection to them. Grouping is a step of making group.Games can be done by applying some games like snake ladder and other games. Tournament is astep of selecting to know the children who understand the materials. Reward is a step of giving a giftto the street children who can finish or win the games and tournament successfully. A reward isexpected to motivate them to study.Key words: 9‐years compulsory education, street children, motivation